2022
DOI: 10.5114/aic.2022.122864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 pandemic on six-month mortality and clinical outcomes of patients with ST-elevation myocardial infarction

Abstract: Introduction:The coronavirus disease 2019 (COVID-19) infection has changed everyday clinical practice, with a shortage of solid data about its implications for ST-elevation myocardial infarction (STEMI) patients.Aim: To evaluate the impact of COVID-19 on 6-month clinical outcomes of patients with STEMI and determine the mortality predictors after STEMI during the COVID-19 pandemic.Material and methods: This prospective observational study was conducted on consecutive STEMI patients who presented to our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…A noteworthy trend in mortality rates among STEMI patients during the pandemic has been observed. A study has shown that there has been a threefold increase in in-hospital mortality for STEMI patients with COVID-19 [16]. Besides, during the pandemic, STEMI patients have been found to have a higher need for circulatory support, worse thrombolysis in myocardial infarction (TIMI) flow, and a significantly higher 30-day mortality rate [1].…”
Section: Outcome and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…A noteworthy trend in mortality rates among STEMI patients during the pandemic has been observed. A study has shown that there has been a threefold increase in in-hospital mortality for STEMI patients with COVID-19 [16]. Besides, during the pandemic, STEMI patients have been found to have a higher need for circulatory support, worse thrombolysis in myocardial infarction (TIMI) flow, and a significantly higher 30-day mortality rate [1].…”
Section: Outcome and Prognosismentioning
confidence: 99%
“…However, COVID-19 patients with STEMI tend to have a higher burden of coronary thrombus compared to non-COVID-19 patients [ 15 ]. Analysis of STEMI outcomes during the pandemic reveals significant challenges, including a threefold increase in in-hospital mortality for STEMI patients with COVID-19 and delays in receiving proper treatment [ 16 ]. Complications such as stent thrombosis and cardiogenic shock are more common, especially among older patients, who also face longer procedure times and higher mortality rates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have investigated that ST-segment elevation myocardial infarction (STEMI) patients with COVID-19-positive have a high in-hospital mortality. [ 11 , 12 ] However, the effect of this finding was finite because of the limited statistical power, and we could not calculate indirect and direct causes of enhancement mortality in COVID-19-positive patients.…”
Section: Introductionmentioning
confidence: 98%